Virtually prepared: designing remote environmental health practicum experiences - Ndoh, Christina E.; Bortey-Sam, Nesta; Moore, Maggie; Ufelle, Alexander (Frontiers in Education, 2024)
The push for virtual education modes continues to grow and develop following unprecedented acceleration during the COVID-19 pandemic. Environmental and occupational health education echoes that demand, where programs are seeing the focus expand from lab-based bench work to include greater practice emphasis in areas such as environmental health equity, environmental justice, environmental policy, and environmental health literacy. Part of the educational foundation for Environmental and Occupational Health MPH programs includes a practicum designed to provide students with "real-world" experience beyond classroom applications. Given the expected increased demand for virtual educational models from students and virtual employees from the professional sector, higher education programs that require practicum experiences must seek innovative approaches that meet both student and employer needs. The University of Pittsburgh's Department of Environmental and Occupational Health is a practicum host site for local universities. Recently, faculty have sought to co-create virtual environmental health practicums in response to requests for these types of opportunities. This article expands upon work on "virtual" or "remote" practicum placements and builds upon best practices to contribute to continuing research in this area. The article also shares insight into creating additional virtual opportunities in the environmental health field. This work presents a case study of the development of a virtual student practicum, documents the processes and procedures followed to develop work grounded in best practices, and shares lessons learned and recommendations for developing future virtual practicums for public health students. The student and practicum host provide reflections on the practicum design and experience.